Suitability and Carrying Capacity of Seagrass for Snorkeling on Tunda Island, Banten - Prafitri Saraswati Darmawan; Wahyuniar Pamungkas; Indah Riyantini; Sri Astuty (Program Pascasarjana, 2020)
The seagrass ecosystem has ecological and economical functions, which can provide benefits to the surrounding community as a conservation area and marine tourism. Studies on the suitability of seagrass ecosystems for marine tourism, especially snorkeling, on Tunda island are needed to support their use. The purpose of this research is to evaluate the suitability and carrying capacity of seagrass ecosystems on Tunda Island, Banten for marine tourism snorkeling. The research was conducted in March - July 2019. The research method carried out was a survey with five observation stations in the seagrass area on Tunda Island. The parameters observed are seagrass cover, seagrass type, fish type, brightness, temperature, depth, current speed, substrate type, salinity, pH, DO, facilities, and infrastructure as well as accessibility. Data analysis was performed in a comparative description between five observation stations. The result of this research showed that station 1 (in north area) and station 4 (in southeast region) had a value of the Tourism Suitability Index in the range of 73.15% - 77.78% and included in the Suitable category, which are potential stations to be developed as snorkeling marine tourism areas. The carrying capacity of the seagrass area for snorkeling tours on Tunda Island, Banten with an area of 11,197 hectares isÂ 44 people per day.Keywords: Marine tourism, regional carrying capacity, regional suitability, seagrass, snorkeling.